Properties of P460-S355 submerged arc welds - Turkmen, Mustafa; Kati, Nida; Kejanli, Haluk; Caligulu, Ugur (Walter de Gruyter Gmbh, 2020)
In this study, the weldability of P460 and S355 steel was investigated by application of the submerged arc welding (SAW) process. In the analyses, the effects of various parameters were handled at different welding speeds, the two levels of the current values of 475 A to 525 A and 525 A to 575 A, commercial submerged additive metals, and commercial aglomera welding powders. A notch impact test was carried on to determine the strength of the joints. Microhardness measurements were made at a Vickers load of 500 g. Optical microscopy and EDS analyses were utilized in the weld zone to investigate the microstructure changes which depend on the welding parameters. The results of this study indicate that P460 steel maintained sufficiently good weldability by application of the submerged welding process.
Keywords: Steel P460; Steel S355J2G3; submerged arc welding; notch impact test; microhardness